Avaliação psicológica de pais em disputa de guarda - Silveira, Jaíne Foletto (2018)
The present research aims to address the psychological evaluation of parents who are in a situation of custody of their children, from the analysis of their personalities through the Five Factors Inventory NEO Revised, NEO-FFI-R, along with the Parenting Styles Inventory. In view of the large number of judicial separations and divorces in Brazil, new family configurations emerge, different from the standard established a while ago. Considering this contemporary reality of the Brazilian families, it is perceived the necessity of studies that approach the theme for a greater scientific knowledge in the area. After evaluating 25 parents (13 women and 12 men) who were competing for custody of their children, it was found that 28% of parents exercised a good parental style, 40% good parental style, 24% regular parental style and 8% risk parental style. Pearson's correlation test showed a negative correlation between agreeableness and relaxed discipline, moderate positive correlation between conscientiousness and moral behavior, positive correlation between neuroticism and relaxed discipline, negative correlation between openness and relaxed discipline, and negative correlation between conscientiousness and negligence.